Cover Picture: Biotechnology Journal 12/2019. Issue 12 (10th December 2019) - Wang, Xuan; Jiang, Xiao‐Ran; Wu, Fuqing; Ma, Yiming; Che, Xuemei; Chen, Xiyue; Liu, Ping; Zhang, Wenbing; Ma, Xi; Chen, Guo‐Qiang
Abstract : Microbial poly‐3‐hydroxybutyrate (PHB) has been produced via microbial fermentation and safely used as feed additives for sea based large yellow croakers and sensitive land based weaned piglets. PHB maybe also PHA could One day replace petrochemical plastics to save animals that ingest discarded plastics. This is reported by Xuan Wang, Xiao‐Ran Jiang, Fuqing Wu, Yiming Ma, Xuemei Che, Xiyue Chen, Ping Liu, Wenbing Zhang, Xi Ma, and Guo‐Qiang Chen in article 1900132 .